CFD Simulation of Melting and Solidification of PCM in Thermal Energy Storage Systems of Different Geometry. (October 2015) - Arena, S; Cau, G; Palomba, C
Abstract: At the Department of Mechanical, Chemical and Materials Engineering of the University of Cagliari an experimental and numerical research project has begun with the aim of developing highly efficient thermal energy storage (TES) systems using phase change materials (PCM) of particular interest in concentrating small-medium scale solar power (CSP) applications. The present work aims to simulate the melting and solidification processes in containing boxes and heat transfer devices of different geometrical features which may constitute the elementary cell of a more complex TES system. Two-dimensional axisymmetric numerical models, developed with COMSOL Multiphysics are considered and used to simulate TES, heat conduction and natural convection. The models are used to determine the temperature profile inside the PCM to identify which configurations are capable of enhancing thermal response between a solid wall and a PCM. The results obtained will be used for comparison with experimental data acquired from a pilot plant under construction in the DIMCM laboratories. At the current stage the laboratory is being brought to completion.